Crosslinking of palm oil polyol based shape memory polyurethane - E.S., Ali (2015)
The effect of palm oil polyol crosslinking on the mechanical and shape memory properties of polyurethane (PU) polymer was investigated and compared with linear PU. The PU was composed of polycaprolactonediol (PCL), palm oil polyol, 4,4-diphenylmethane diisocyanate (MDI) and 1,4-butanediol (BD). Palm oil polyol was introduced due to its large number of functional groups, hyperbranched structure and easy availability. The shape fixity decreased with addition of palm oil polyol while shape recovery increased and showed an optimum value with the addition of palm oil polyol. The mechanical properties improved with the addition of palm oil polyol in regards with linear PU. Copyright © (2012) Asian-Australasian Association for Composite Materials (AACM).